THE ROLE OF TEACHERS AND STUDENTS IN DEALING WITH EDUCATION IN THE PANDEMIC TIME OF COVID-19: PERAN GURU DAN MAHASISWA DALAM MENGHADAPI PENDIDIKAN PADA WAKTU PANDEMI COVID-19 - Herrie Kurniawan (SOSIOEDUKASI, 2020)
purpose of writing this article is to discuss the role of teachers and students in facing education during the Covid-19 pandemic. This writing method uses descriptive analysis method by reviewing the education system that occurred during the Covid-19 pandemic and seeing the role between teachers and students in facing the world of education during the Covid-19 pandemic. This descriptive analysis method will be collected and some reinforcing data will be provided for educational problems during the Covid-19 pandemic. The results of this writing will be useful in seeing how effective the education and learning system is for teachers and students in facing the Covid-19 pandemic and also whether education in Indonesia is ready to face the new learning system, especially for teachers and students who are facing online learning. during the Covid-19 pandemic.